Role of Vitamin B12, Folic Acid and Oxidative Damages, in Serum of Patients with Vitiligo - Sherief Mahdy Hussein (Journal of Global Pharma Technology, 2016)
Background: Vitiligo is a chronic common disease which may cause as a result of oxidative stress which is proposed to implicate in its etiopathogenesis. Vitiligo is an autoimmune disease affecting skin, hair and oral mucosa. This disease is characterized by a loss of melanin. Disturbance of thyroid hormones has been known as a key trigger of this pathology. Objective: The aim of this study is to determine the levels of vitamin B12, folic acid , oxidative stress (lipid peroxidation ;MDA),total antioxidant capacity (TAC), Paraoxanase (PON1)in serum of patients with vitiligo compared to matches control group. Materials and subjects: The study included 42 patients from Egyptian population suffering from generalized vitiligo (29 male patients and 13 female patients; mean age 35.1 years; ranging from 28-45 years and 36 healthy volunteers as control group (22 male patients and 14 female patients; mean age 36.2 years; ranging from 25–47years). Vitiligo patients were recruited from Medical research center of excellence of National Research Centre, Egypt, during interval of 6 months (1 October, 2018 to 31 March , 2019). Vitiligo diagnosis is based on if areas of patient's skin, hair or eyes lose coloring and confirmation is done by using Wood’s lamp. Blood samples were obtained from the patients and controls. PON1, MDA, TAC vitamin B12 (vit.B12) and folic acid biomarkers were analyzed in serum samples of both control and vitiligo patients. Results : The present results declared significant elevation of oxidative stress ; MDA (+159.26), which is associated with significant decrease in PON(-34.10) ,TAC (-35.89),vitamin B12(-53.41) and folic acid (-89.23) in vitiligo patients compared to control group. Conclusion: Oxidative stress and antioxidant balance are strongly implicated in the vitiligo patients .Vitiligo disease should be examined for multifactorial such as homocysteine levels for a possible implication due to the postulation in the pathogenesis of vitiligo based on the previous findings . Moreover, the therapeutic role of supplementation with Vitamin B12/folic acid in vitiligo needs to be studied further.Keywords: Autoimmune disease, Melanin loss, Oxidative stress, Vitiligo, Vit. B12, Folic acid, TAC,PON.